Association of probiotic supplementation and cardiovascular risk profiles of patients with coronary artery disease—a cross-sectional analysis of the NHANES database between 1999–2019 - Palathinkara, Murali; Aljadah, Michael; Thorgerson, Abigail; Dawson, Aprill Z.; Widlansky, Michael E. (Frontiers in Nutrition, 2025)
BackgroundAtherosclerotic cardiovascular disease (ASCVD) is a chronic inflammatory disease that leads to adverse events such as myocardial infarctions and stroke. Gut microbiome modulation is a promising target to reduce chronic inflammation and improve outcomes for patients with coronary artery disease (CAD). Risk profile patterns of CAD patients who target gut health with probiotics could provide insight into how gut modulation improves CAD clinical biomarkers. This study aims to evaluate the association between probiotic use and clinical markers of known atherosclerotic risk factors, in patients with CAD.MethodsWe conducted a cross-sectional large-database study using National Health and Nutrition Examination Survey (NHANES) data from years 1999–2020. The cohort included adults with at least a diagnosis of coronary heart disease, angina, and heart attack or two of the following: diabetes, high blood pressure, and high cholesterol. Analyses of clinical biomarkers compared probiotic to non-probiotic groups, between probiotic type groups, and between probiotic supplement strains.ResultsOur cohort included 14,992 survey responders. After weighting, this sample represented 46,217,980 US adults. There were 4,062,022 adults exposed to probiotics, 763,288 to probiotic supplements and 3,179,008 to probiotic foods. Probiotic exposure was associated with lower A1c (p < 0.001), lower triglycerides (p < 0.001), lower ASCVD risk score (p = 0.01) and higher HDL-C (p < 0.001). Probiotic supplement exposure was associated with lower LDL-C (p = 0.003) and total cholesterol (p = 0.047).ConclusionOur study reinforces the beneficial association between probiotic ingestion and cardiovascular health in patients with existing atherosclerotic disease. Further studies to better determine potential mechanistic connections between the gut microbiota on cardiovascular risk factors is warranted.